Clinical characteristics and management outcomes of pediatric patients with Coats disease complicated with retinoschisis (retinal cyst) - Tingyi Liang; Shaochi Zhang; Xiang Zhang; Xiaohan Wang; Xunda Ji; Peiquan Zhao (Frontiers in Medicine)
PurposeTo present the clinical characteristics and management outcomes of Coats disease with retinoschisis (retinal cyst).MethodsThis was a retrospective review of 13 eyes from 13 consecutive Coats disease patients with retinal cyst. Clinical findings from multimodal ophthalmic imaging were recorded to characterize retinal cyst in Coats disease. All eyes were initially treated with endolaser photocoagulation combined with external drainage of cystic fluid and intravitreal ranibizumab injection. Patients were subsequently followed up to analyze anatomic and visual outcomes.ResultsAll retinal cysts were associated with extensive retinal exudation; 3 eyes (23.1%) presented with exudative retinal detachment. A total of 92.3% (12/13) of the retinal cysts were located in the inferotemporal quadrant. Fluorescein angiography demonstrated telangiectasia surrounding and/or at the edge of the retinal cyst. Eleven eyes (84.6%) underwent endolaser photocoagulation via a nonvitrectomy approach, and 2 eyes (15.4%) underwent endolaser photocoagulation after vitrectomy due to the presence of epiretinal membrane. An average of 1.5 additional laser photocoagulation sessions was performed per patient. After a median follow-up of 23 months (range, 11–33 months), all eyes demonstrated retinal cyst resolution and no active disease. Subretinal fibrosis was observed in 9 eyes (69.2%); of these, 8 had macular subretinal nodules. In total, 30.8% of the eyes had a final vision ≥20/200.ConclusionThe presence of retinoschisis (retinal cyst) in Coats disease is strongly associated with retinal telangiectasia and exudation and is indicative of active vascular disease requiring effective ablative treatment. We propose a novel approach, endolaser photocoagulation combined with external drainage of cystic fluid and intravitreal ranibizumab injection, which was effective in achieving final anatomic improvement with retinal cyst resolution.